If it's not what You are looking for type in the equation solver your own equation and let us solve it.
45(h-1)=450-55h
We simplify the equation to the form, which is simple to understand
45(h-1)=450-55h
Reorder the terms in parentheses
+(+45h-45)=450-55h
Remove unnecessary parentheses
+45h-45=+450-55h
We move all terms containing h to the left and all other terms to the right.
+45h+55h=+450+45
We simplify left and right side of the equation.
+100h=+495
We divide both sides of the equation by 100 to get h.
h=4.95
| 6x+4=4x-1 | | 25c^2+90cp+81p^2=0 | | -46=-6+5p | | 7x+8+3x-3=25 | | 2.5m+(-3.5m)-4=56 | | h-135=25 | | 9.3.96=4.7p+8.7p-2.6p | | -x^2+576=0 | | 16v^2-24v+9=0 | | 14.2-0.89+2.8-0.7q=10-1.5q-5.1 | | y=1/4x-5 | | -2.4a+3.7=-16.1+3.1a | | 6a+7m+9m=11 | | 0=6n-5 | | f+11/2=41/4 | | -8w-(-3)=-53 | | 6-2.8=0.8b+1.2 | | f(x)=x^3+5x^2+7x+3 | | 9m-22=-6+5m | | 4(x+4)=100 | | 5a+9=18 | | 2x^2-9=-107 | | -8w(-3)=-53 | | 6y-12-4y=8 | | h-125=75 | | 6-2.8=0.8+1.2 | | 6-6=8x+6x | | 12x-4=40 | | (x/2)+(x-12)+x=53 | | 9-2d=-31 | | 12x+3-3x=12 | | 2x-117+1/2x+16+x-27=180 |